Legal Awareness Of Hospitals In The Implementation Of The Regulation Of The Minister Of Health No. 44 Year 2018 On The Effectuation Of Hospital Health Promotion (Study At Hj. Fatimah Sulhan Pku Muhammadiyah Demak Hospital - Ahmad Ghufron; Rizka Rizka; Wardah Yuspin (IHSA Institute, 2024)
Health Promotion is a process to empower the society through activities to inform, influence and assist the society to play an active role to support behavioral and enviromental changes and maintain and improve health towards optimal health status. The purpose of this study was to analyze the awareness of the implementation of PKRS based on Permenkes No. 44 of 2018 at Hj. Fatimah Sulhan PKU Muhammadiyah Demak Hospital. This research uses empirical research. The results of this study explain that hospitals in the implementation of PKRS based on Permenkes No. 44/2018 focus on 2 aspects, namely PKRS management and fulfillment of PKRS standards. In the preperation carried out, hospitals must consider the rules of the PKRS guidelines that have been regulated in the regulations. These regulations must not contradict but ini making internal rules, hospitals can add according to the technical needs of PKRS. The hospital has adjusted the PKRS guidelines and work program with the guidelines regulated by Permenkes No. 44/2018